カイヨウ カンソク センヨウセン ニヨル ナンキョクカイ ノ タイキ エアロゾル カンソク - 長田, 和雄; オサダ, カズオ; 原, 圭一郎; ハラ, ケイイチロウ; 矢吹, 正教; ヤブキ, マサノリ; 西田, 千春; ニシダ, チハル; 小林, 拓; コバヤシ, ヒロシ; 三浦, 和彦; ミウラ, カズヒコ; et al. (2010)
P(論文) 南極海における大気エアロゾル粒子の粒径分布やイオン成分濃度,先駆ガス濃度の時空間分布を調べるために,「白鳳丸」や「タンガロア」,「海鷹丸」による船上観測をおこなった.海況の穏やかな南極海での観測では,直径0.1 μm以上の既存エアロゾル粒子数濃度が著しく低い条件下で,高濃度の核生成モード粒子(直径<20 nm)を観測することがあった.逆に,既存のエアロゾル粒子数濃度が高い場合には,核生成モード粒子数濃度の増加は見られなかった.2005年1月に「海鷹丸」で観測したリュツォ・ホルム湾洋上のエアロゾル粒子中主要イオン濃度は,昭和基地で1月に観測される平均的な濃度とほぼ同じであった.「海鷹丸」と昭和基地との同時観測の結果,短時間に凝縮核数濃度が高くなるイベントの場合には,核生成モードやエイトケンモード粒子の粒径分布は両者で大きく異なっていた. To investigate spatial and temporal variation of number-size distribution of atmospheric aerosol particles in the Antarctic Ocean, atmospheric observations were conducted on research vessels: Hakuho-maru, Tangaroa, and Umitaka-maru. Concentrations of ionic constituents in aerosols and precursor gases (SO_2 and NH_3) were also measured during the cruises. Concentrations of nucleation mode particles (<20 nm in diameter) were often high under the conditions of very low number concentrations of preexisting aerosol particles larger than 0.1 μm in diameter, when the ocean was calm. Nucleation mode particles did not appear when concentrations of preexisting aerosols were high. Major ionic concentrations of aerosols at Lutzow-Holmbukta observed by Umitaka-maru in January 2005 were almost the same as average values of those in January at Syowa Station. Especially for short-term increasing events in condensation nucleus concentration, large differences were found for number size-distributions of nucleation and Aitken mode particles between Syowa Station and Umitaka-maru in Lutzow-Holmbukta. departmental bulletin paper